2018
DOI: 10.1111/ffe.12793
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue strength of spring steel with small scratches

Abstract: In compression coil springs subjected to cyclic load, fatigue cracks can sometimes initiate and propagate from scratch‐like small defects produced during the manufacturing process and degrade the fatigue strength. In this study, torsional and rotating bending fatigue tests were conducted to examine the fatigue behavior of a high‐strength spring steel (JIS G 3561, SWOSC‐V) in the presence of small scratches. The sensitivity of the HCF and VHCF strength to small scratches was evaluated based on the area paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 37 publications
1
19
0
1
Order By: Relevance
“…It has been reported that for various metallic materials, the fatigue limit as a crack‐growth threshold can accurately be predicted by the area parameter model . This model states that Δ Κ th at a stress ratio of −1 depends on the size of the initial crack or defect and the hardness of the material, expressed by the following equation: normalΔΚth=3.3×103()italicHV+120area1/3. The unit is MPa m for Δ Κ th .…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that for various metallic materials, the fatigue limit as a crack‐growth threshold can accurately be predicted by the area parameter model . This model states that Δ Κ th at a stress ratio of −1 depends on the size of the initial crack or defect and the hardness of the material, expressed by the following equation: normalΔΚth=3.3×103()italicHV+120area1/3. The unit is MPa m for Δ Κ th .…”
Section: Resultsmentioning
confidence: 99%
“…This equation is widely used for the prediction of the fatigue limit of numerous metallic materials with small defects and cracks. [30][31][32][33][34][35][36][37] It is worth noting that the model has been proven to give an accurate forecast of the fatigue limit of the Ti-6Al-4V alloy with small defects and cracks of diverse sizes and dimensions. [38,39] In the prior study by the author et al, the local R value was calculated according to the residual stress distribution in Equation 2, thereby enabling the successful prediction of the fatigue limit of an FOD specimen.…”
Section: Discussionmentioning
confidence: 99%
“…This observation can be attributed to the formation of the homogeneously distributed sub-micron size grains and ultra-fine nano carbides with high volume ratio after the deep cryogenic treatment as also discussed in the previous section. Fatigue tests were conducted under five different loads by using three samples for each load, Table 4. The high cycle (> 10 4 ) fatigue tests were selected to determine the fatigue strength of the specimens since the cryogenic treatment has no considerable contribution to the fatigue strength in low cycle (< 10 4 ) fatigue regime due to the possible failure in locking of the dislocations by fine martensite grains in this regime [33].…”
Section: Mechanical Properties Of Heat Treated Specimensmentioning
confidence: 99%
“…They are primarily utilized in the automotive industry as leaf springs and anti-roll bars, which are suspension elements used in various highway and railroad vehicles [2,3]. These suspension components generally have the tempered-martensitic microstructure to fulfill the necessary mechanical competence since they are constantly exposed to a dynamic mechanical stress [4].…”
Section: Introductionmentioning
confidence: 99%